Corrosion Inhibition of Al-Si-Cu Alloy in the Basic Media by UsingSix Inhibitors at Four Temperatures - Baghdad Science Journal (مجلة بغداد للعلوم)
The research involved attempt to inhibit the corrosion of Al-Si-Cu alloy in 2.5x10-3 mol.dm-3 NaOH solution (pH=11.4) by addition of six different inhibitors with three concentrations (1x10-3, 1x10-2, and 0.1 mol.dm-3). These inhibitors include three organic materials (sodium acetate, sodium benzoate, and sodium oxalate) and three inorganic materials (sodium chromate, disodium phosphate, and sodium sulphate). The data that concerning polarization behaviour are calculates which include the corrosion potential (Ecorr) and current density (icorr), cathodic and anodic Tafel slopes (bc & ba), and polarization resistance (Rp). Protection efficiency (P%) and activation energy (Ea) values were calculated for inhibition by the six inhibitors. The results indicated the effect of temperature on the inhibition in basic media.